Sifat Fisis, Mekanis Serta Keawetan Batang Kelapa Hibrida - Istie Sekartining Rahayu (Jurnal Ilmu Pertanian Indonesia, 2006)
Nowadays, wood industry in Indonesia suffers from lack of wooden raw material because of the demand is greater than the supply. In order to solve this problem, we need to enhance the use of wood by optimalizing the use of wooden raw material wich has a great potensial, but not well used, for example hybride coconut wood. The purpose of this research were to determine physical, mechanical and chemical properties of hybride coconut wood and its vertically and horizontally variation in order to optimalize the use of hybride coconut wood. This research used three hybride coconut steems, the 6 cm disks were extracted from each stem at 1, 4, 7, and 10 m heights. The analyze of vascular bundle and parenchyma consisted of covered area per cm2 and their chemical composition. Hybride coconut wood had a low specific gravity because vascular bundle covered area was lower than parenchyma per cm2 and low wood substance portion. Low specific gravity caused low mechanical properties. Hight moisture content (specially fresh one) was cause by sugar and starch extractives which had high hygroscopic ability. These extractives content also caused it to be easily attacked by wood destroying factors. Parenchyma covered area per cm2 caused high sugar and starch content. Height and depth factors were visible influence at almost all basic properties of vascular bundle and parenchyma at different level.